The Influence of a Volume Scale-Factor on Scattering Coefficient Effects in Room Acoustics. Issue 2 (June 2014) - Shtrepi, Louena; Astolfi, Arianna; Rychtáriková, Monika
Acoustic scattering has become an important input parameter in geometric models, and in research concerning the enhancement of auralized sound. This contribution deals with a comparison of four scaled prediction models of the same concert hall and a study of the scattering coefficient prominence in simulations, while the size of the concert hall doubled. The hall is fan shaped with an aspect ratios of about 4.5:2.8:1 and has typical auditorium features, such as a stage and a raked audience area. The influence of a volume scale-factor on the scattered sound effects on the prediction of the objective room acoustic parameters, that are, EDT, C 80, D 50, LF 80 and G, has been investigated. Five different alternatives, in which scattering coefficient percentage values of 10, 30, 50, 70, and 90%, respectively, were applied separately and combined to the interior surfaces of the ceiling, side and rear walls, have been simulated. An analysis has been performed studying the results of the objective room acoustical parameters predicted, through simulations carried out with two kinds of software: Odeon 11.00 and CATT-Acoustic v 8.0.